2021
DOI: 10.1016/j.psj.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: The use of ammonia gas for Salmonella control in poultry litters

Abstract: A new poultry litter disinfection methodology against pathogenic Salmonella spp. serovars using gaseous ammonia is proposed in this study. In the laboratory, the poultry litter was disposed into plastic containers and experimentally contaminated with 3 Salmonella spp. serovars separately. Positive and negative control groups were tested. With a system of hoses, 1% gaseous ammonia was injected into the containers in cycles for 48 h. Samples of the poultry litter wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Several studies have demonstrated the antimicrobial effects of NH 3 on Salmonella in poultry litter and solutions ( 19 , 28 , 31 , 33 35 ). However, previous work in poultry litter has often been performed using NH 3 gas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the antimicrobial effects of NH 3 on Salmonella in poultry litter and solutions ( 19 , 28 , 31 , 33 35 ). However, previous work in poultry litter has often been performed using NH 3 gas.…”
Section: Discussionmentioning
confidence: 99%
“…The alkaline pH of the buffer solutions likely served as an added stressor against Salmonella . Previous studies in poultry litter and manure have used various levels of NH 3 gas to demonstrate its antimicrobial effects on Salmonella ( 28 , 31 , 33 ). However, these concentrations of NH 3 gas may not be feasibly generated as a result of natural ammonia production in commercial poultry litter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that S. Typhimurium could be reduced by 8 log CFU g −1 in poultry manure dried to 10% moisture and treated with 1% ammonia gas for 72 h at 20°C. In another study, Mendonça et al (2021) used ammonia gas (2411 ppm) to decontaminate poultry litter in broiler houses contaminated with S. Heidelberg. Studies on poultry litter composting have also suggested that ammonia production may contribute to the reduction of Salmonella (Erickson et al, 2014;Shepherd et al, 2010;Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…pH, water activity) (Eriksson De Rezende et al, 2001; Payne et al, 2002, 2007). Water activity (a w ), pH, microflora and ammonia are factors that have been shown to influence the survival of Salmonella in poultry litter and manure (Alexander et al, 1968; Bucher et al, 2020; Erickson et al, 2004; Himathongkham et al, 1999; Himathongkham & Riemann, 1999; Mendonça et al, 2021; Payne et al, 2002, 2007; Soliman et al, 2009; Turnbull & Snoeyenbos, 1973). Poultry litter surveys have reported a w levels ranging from 0.77–1.00 (Carr et al, 1994, 1995; Chinivasagam et al, 2012; Hayes et al, 2000; Opara et al, 1992; Payne et al, 2006).…”
Section: Introductionmentioning
confidence: 99%